Sistem Informasi Persediaan Barang pada Ahass Motocare Cikampek - Abdullah, Tohir; Alfarizi, Salman; Gunawan, Deni; Basri, Hasan; Mulyawan, Alif Rizqi; Ichsan, Nurul (PROFITABILITAS, 2021)
Inventory has an important meaning because it will affect the level of production and sales. Without an inventory of goods the company will not run smoothly. At this time trading companies are faced with very tight competition, therefore companies must provide fast services in managing merchandise inventory. A good inventory system can help increase company profits, especially in the services provided by Ahass Motocare Cikampek. If the inventory of merchandise is fulfilled, the quality of its services will increase and will be faster in handling consumer demand. The process of recording merchandise inventory at Ahass Motocare Cikampek uses periodic inventory recording, which only records purchases of merchandise and a physical check of inventory at the end of the period or what we call stock taking. In the process of recording and calculating determined by the company, it still uses a simple method by writing on a note. So that in making financial statements, data is often lost because the notes used are often lost. It is necessary to create an accounting information system and use applications to support the activities that occur at Ahass Motocare Cikampek so that they can be carried out more quickly and efficiently. And the preparation of financial reports can be done more quickly and avoid manipulation of financial data.